Efficacy of a novel dentifrice containing bioactive glass-ceramic for dentinal hypersensitivity: A double-blind randomized controlled trial in Chinese adults - Li, Jia; Han, Qi; Zhang, Li; Zhang, Jing; Yin, Wei; Zhong, Yisi (Journal of dentistry, 2024)
To assess the efficacy and safety of a toothpaste containing 7.5 % HX-BGC in combating dentinal hypersensitivity. A single-center, randomized, double-blind, three-group parallel-controlled design was employed, with Schiff Index and Yeaple Index as measurement indicators. The study evaluated the effectiveness of HX-BGC toothpaste, NovaMin toothpaste, and a negative control toothpaste without desensitizing agents. Eligible subjects underwent baseline examination after a 2-week washout period, and those meeting inclusion criteria and not meeting exclusion criteria entered the study. Participants were randomly assigned to use one of the three toothpastes. Follow-up examinations were conducted immediately after a single use and at 2, 4, and 6 weeks. Intra-group and inter-group comparisons were made for Schiff and Yeaple indices. Safety of the experimental toothpastes was assessed through participant feedbacks and oral soft tissue examinations. Subjects in the three groups were balanced in terms of age and gender distribution, with no baseline differences in indicators. Immediately after a single application of toothpaste, Yeaple indices increased, and Schiff indices decreased, with no significant differences among the groups. After 2 weeks of continuous use, Yeaple indices increased in all groups, with significant differences observed between the HX-BGC group and the other two groups. Schiff indices decreased in all groups, with the NovaMin group showing significant differences compared to the negative control group. At weeks 4 and 6, both indices in the HX-BGC group and the NovaMin group were significantly better than those in the negative control group, with the HX-BGC group outperforming the NovaMin group in the Yeaple index. No serious adverse reactions related to the study products were observed or reported by any participants. This clinical trial confirmed the efficacy of HX-BGC in anti-dentinal hypersensitivity and supported the clinical application of the dentifrice containing HX-BGC. Compared to the negative control group, both HX-BGC and NovaMin toothpaste groups demonstrated more significant effects in combating dentinal hypersensitivity. No adverse reactions related to the experimental toothpastes were observed.